Using combined resonance on low sound frequencies for cultivation of microorganisms - Мельник, Вікторія Миколаївна; Карачун, Володимир Володимирович; Шибецький, Владислав Юрійович; Фесенко, Сергій Віктрович (Technology audit and production reserves, 2014)
The possibility of increasing the productivity and quality of the cultivation of microorganisms in liquid media by the sound wave irradiation below the cutoff frequency is studied. The possibilities of the combined resonance of the working mixture of the interconnected chambers are shown and some results for determining the sound beam direction are given. The results can be used in microbiology for improving the cultivation of microorganisms in liquid media, in particular in the manufacture of biologically active fluids and vaccines. Artificial formation of low-frequency circular vibrations in the connected camera material allows without additional complications facilitating the design for the cultivation of microorganisms to intensify the energy state of the working fluid, getting rid of the passive energy zones and intensifying the mass transfer and aeration that will increase the productivity and quality of manufacturing the product. The practical implementation is the creation of combined resonance as the equality of the frame circumference and the length of the circumferential (longitudinal) wave in the camera material.